The Urgency of Obligation To Establish A Legal Entity For Foreign Over-The-Top (OTT) Service In Indonesia - Ibadi, Mohamad; Sukarmi; Ruslijanto, Patricia Audrey (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
This study evaluates the effectiveness and legal urgency of requiring foreign Over-the-Top (OTT) service providers to establish a legal entity in Indonesia. The existing regulatory framework—comprising the Income Tax Law, the Harmonization of Tax Regulations Law, and Circular Letter No. 3/2016—remains limited and has not fully adapted to digital economic realities, particularly the principle of significant economic presence. Using a normative juridical method combined with Economic Analysis of Law, this study finds that foreign OTT operations have created legal uncertainty due to regulatory fragmentation, lack of physical presence requirements, and weak enforceability. Comparative analysis with the U.S. economic nexus model demonstrates the need for Indonesia to shift towards digital presence–based taxation. The study concludes that harmonizing tax, communications, and trade regulations—supported by risk‑based and adaptive digital governance—is essential to strengthening fiscal justice, consumer protection, and national digital sovereignty.